USE OF UNMANNED TRANSPORTATION VEHICLES IN DELIVERY OF ROLLED METAL PRODUCTS AND NAVIGATION PROBLEMS - Anton I. Izotov (International Journal of Advanced Studies)
The article offers a comprehensive analysis of unmanned automotive vehicles in logistics, focusing particularly on the transportation of rolled steel products. It discusses key aspects of integrating and operating UAVs, highlighting their economic efficiency, safety, and environmental sustainability. Current safety issues in transporting rolled steel, including cargo securing methods and inertial force considerations, are thoroughly examined. Detailed insights into modern navigation technologies and safety systems like LiDAR and radars applied in unmanned vehicles are provided. Additionally, the article presents data on leading Russian companies in UAV development and implementation, such as Evocargo, KamAZ, SberAutoTech, and Starline, detailing their achievements and prospects in this field.